Analisis Pengaruh Kinerja Keuangan terhadap Perataan Laba pada Perusahaan Perbankan Terbuka di Indonesia - Pariang Siagian (Bina Nusantara University, 2015)
The objective of this research is to analyze and identify if there is any influence or not of some financial ratios of go public banking companies on income smoothing index individually or simultaneously. Income smoothing is a form of earning management wich reflect the banking economic or financial performance result, likes the Non Performance Loan (NPL), Posisi Devisa Neto (PDN), Loan Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) and Return On Assets (ROA). Those the indicators filled and used as the representation of financial performance of banking according to regulation of Bank Indonesia No.13, year 2011. All of these ratios uses as the independent variables in this research, while the Income Smoothing Index as the dependent variable. There are eight of go public banking companies listed in BEI in 2008 – 2012 periods that is used as samples, which are selected by purposive sampling. This study has found that there is no the impacts of each independent variables NPL, PDN, LDR, CAR and ROA to the dependent variable Income Smoothing, individually and simultaneously.